THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN ARABIC LANGUAGE LEARNING AT MAN 11 JAKARTA - Herdiani, Salvia; Maswani; Tsaniya, Syifa Bilqis; Refaldi, Muhammad (SHAWTUL ARAB, 2025)
This study explores the implementation of Kurikulum Merdeka (Independent Curriculum) in Arabic language learning at Madrasah Aliyah Negeri (MAN) 11 Jakarta, a pivotal shift in Indonesia's education system aimed at fostering deeper learning and teacher autonomy. The research primarily sought to understand how the curriculum is implemented, the major challenges teachers face, and the innovative strategies employed to overcome these barriers. Utilizing a qualitative case study approach, data was meticulously collected through in-depth interviews, participatory observation, and comprehensive document analysis, involving both teachers and students. Key findings reveal that teachers encounter significant challenges, including limited relevant resources, low communicative interaction, and students' perception of Arabic merely as a formal           obligation, compounded by heterogeneous student backgrounds. Despite these hurdles, teachers demonstrated remarkable initiative, developing innovative differentiation strategies like contextual videos, intensive study groups, and digital projects. These approaches notably boosted student motivation and confidence, demonstrating the curriculum's adaptive potential. The study concludes that the successful implementation of Kurikulum Merdeka critically depends on proactive teacher agency and creative adaptation to complex realities, underscoring the need for synergistic support in policy, resources, and training.